The Wuhan Twin Birth Cohort (WTBC). (27th June 2017) - Zhao, Jinzhu; Yang, Shaoping; Peng, Anna; Qian, Zhengmin; Xian, Hong; Chen, Tianjiao; Dong, Guanghui; Zhang, Yiming; Hu, Xijiang; Chen, Zhong; Cao, Jiangxia; Song, Xiaojie; et al.
Abstract : The Wuhan Pre/Post-Natal Twin Birth Registry (WPTBR) is one of the largest twin birth registries with comprehensive medical information in China. It recruits women from the first trimester of pregnancy and their twins from birth. From January 2006 to May 2016, the total number of twins enrolled in WPTBR is 13, 869 twin pairs (27, 553 individuals). The WPTBR initiated the Wuhan Twin Birth Cohort (WTBC). The WTBC is a prospective cohort study carried out through incorporation of three samples. The first one comprises 6, 920 twin pairs, and the second one, 6, 949 twin pairs. Both are population-based samples linked to the WPTBR and include pre- and post-natal information from WPTBR. The second sample includes neonatal blood spots as well. Using a hospital-based approach, we recently developed a third sample with a target enrolment of 1, 000 twin pairs and their mothers. These twins are invited, via their parents, to participate in a periodic health examination from the first trimester of pregnancy to 18 years. Biological samples are collected initially from the mother, including blood, urine, cord blood, cord, amniotic fluid, placenta, breast milk and meconium, and vaginal secretions, and later from the twins, including meconium, stool, urine, and blood. This article describes the design, recruitment, follow-up, data collection, and measures, as well as ongoing and planned analyses at the WTBC. The WTBC offers a unique opportunity to follow women from prenatal to postnatal, as well as follow-up of their twins. This cohort study will expand the understanding of genetic and environmental influences on pregnancy and twins' development in China.